Gender and climate change: Do female parliamentarians make difference? - Astghik Mavisakalyan; Yashar Tarverdi (Global Labor Organization (GLO), 2018)
This paper investigates whether female political representation in national parliaments influences climate change policy outcomes. Based on data from a large sample of countries, we demonstrate that female representation leads countries to adopt more stringent climate change policies. We exploit a combination of full and partial identification approaches to suggest that this relationship is likely to be causal. Moreover, we show that through its effect on the stringency of climate change policies, the representation of females in parliament results in lower carbon dioxide emissions. Female political representation may be an underutilized tool for addressing climate change.
Keywords: D70; J16; Q54; Q58; 330; gender; political representation; climate change; environmental policy